Effect of Marketing Mix on Decision to Choose People's Business Credit - Fitriany Fitriany (YUME : Journal of Management, 2021)
AbstrakThis study aims to determine the Effect of Marketing Mix on the Decision to Choose People's Business Credit (KUR) at Bank Mandiri Makassar Branch. This study involved 82 respondents who are active customers at Bank Mandiri Makassar Branch. Data were collected by distributing questionnaires to all respondents. Then the data analysis technique uses multiple linear regression analysis using SPSS softmare version 24. The implications of this research are that it can be used as input or consideration for banking companies to implement the marketing mix in increasing the number of people's business credit customers (KUR) and the results of this study indicate that the product, price, promotion, location, employees, physical facilities and service processes have a significant influence on the decision to choose people's business loans at PT. Bank Mandiri (Persero) Tbk. Makassar Branch. Keywords: product, price, promotion, location, employees, physical facilities, service process, people's business credit.